Fast detection method for IC card data integrity protection mechanism - Tang Zhongze; Huang Xiaopeng; Liu Qi (Dianzi Jishu Yingyong, 2025)
This paper introduces the detection methods for data integrity protection mechanism of integrated circuit (IC) card. An improved power-off-testing theory is proposed aiming at the limitations and shortcomings of traditional single-command power-off detection methods, to detect and verify IC card transaction protection mechanism during data recovery process. Using time statistics and power consumption statistics, the effective time zone for power-off testing is calculated to improve testing efficiency. Finally, the effectiveness of the fast detection method for data integrity protection mechanism is verified by experimental results.